Teaching Writing in Lower-secondary English Classes - Krištofová, Martina (Univerzita Pardubice, 2021)
This bachelor thesis deals with developing writing skills in the context of teaching writing in lower-secondary schools. Firstly, the theoretical part defines communicative competence as an aim of teaching foreign languages. After that, the paper focuses on the current approach to teaching writing and discusses various approaches and types of tasks developing this skill. In the practical part, a research is conducted with the aim to find out experience and opinions of the teachers regarding teaching writing.
Výuka psaní v hodinách anglického jazyka na druhém stupni ZŠ
Keywords: řečová dovednost psaní; komunikační kompetence; přístupy; zkušenosti; názory; writing skills; communicative competence; approaches; tasks; experience; opinions